On interpreters of logic programming systems - Semyon A. Nigiyan; Aram M. Hambardzumian (Изд-во НАН РА)
We introduce the notions of totally resolving and totally complete interpreters for Horn programming languages. We prove the existence of totally complete interpreter (an interpreter which gives all the answers for a query if the query is a logical consequence of the program) for any Horn programming language and existence of totally resolving interpreter (an interpreter which gives all the answers for any program and query) for languages whose programs have ¯nite templates of their least models. We also consider problems of total completeness and total resolvability for PROLOG interpreter from viewpoint of some (natural) program transformations and prove that it is not possible to make the interpreter totally complete.
Keywords: Mathematics; Computer software